Genetic Variants of the DSF Quorum Sensing System in Stenotrophomonas maltophilia Influence Virulence and Resistance Phenotypes Among Genotypically Diverse Clinical Isolates - Yero, Daniel; Huedo, Pol; Conchillo-Solé, Oscar; Martínez-Servat, Sònia; Mamat, Uwe; Coves, Xavier; Llanas, Ferran; Roca, Ignasi; Vila, Jordi; Schaible, Ulrich E.; Daura, Xavier; Gibert, Isidre (Frontiers in Microbiology, 2020)
The pathogenicity of Stenotrophomonas maltophilia is regulated in part by its quorum sensing (QS) system. The main QS signaling molecule in S. maltophilia is known as diffusible signal factor (DSF), and the rpf gene cluster is responsible for its synthesis and perception. Two cluster variants have been previously described, rpf-1 and rpf-2, which differ basically in the conditions under which DSF is produced. Here, correlations between the rpf variant and antibiotic susceptibility, LPS electrophoretic profiles and virulence-related phenotypes were evaluated for a collection of 78 geographically and genetically diverse clinical strains of S. maltophilia. In general there were associations between previously established genogroups and the genetic variant of the rpf cluster. However, only few genotype-phenotype correlations could be observed. Resistance to the β-lactam antibiotics ceftazidime and ticarcillin was associated with strains carrying the rpf-1 variant, whereas strains of variant rpf-2, particularly those of genogroup C, showed higher resistance levels to colistin. Strains of variant rpf-2 were also significantly more virulent to Galleria mellonella larvae than those of rpf-1, most likely due to an increased ability of rpf-2 strains to form biofilms. A comparative genomic analysis revealed the presence of proteins unique to individual genogroups. In particular, the strains of genogroup C share an operon that encodes for a new virulence determinant in S. maltophilia related to the synthesis of an alternative Flp/Tad pilus. Overall, this study establishes a link between the DSF-based QS system and the virulence and resistance phenotypes in this species, and identifies potential high-risk clones circulating in European hospitals.